The magic finger - Dahl, Roald; Blake, Quentin (New York : Puffin Books, 2009)
Angered by a neighboring family's sport hunting, an eight-year-old girl turns her magic finger on them.
Originally published New York : Harper & Row, 1966.
Keywords: Hunting -- Fiction; Magic -- Fiction